2021
DOI: 10.3389/fphys.2021.730935
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Hypoxia on Triglyceride Levels

Abstract: Hypoxia is a condition during which the body or specific tissues are deprived of oxygen. This phenomenon can occur in response to exposure to hypoxic environmental conditions such as high-altitude, or because of pathophysiological conditions such as obstructive sleep apnea. Circumstances such as these can restrict supply or increase consumption of oxygen, leading to oxyhemoglobin desaturation and tissue hypoxia. In certain cases, hypoxia may lead to severe health consequences such as an increased risk of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…A study have showeded increased sympathetic activation and up-regulation lipolysis under hypoxia exposure [27]. Consistent with this hypoxia exposure for 14 days in mice significantly increased adipocyte lipolysis and elevated NEFA levels [1]. Several studies have also demonstrated that reduced oxygen supply in the air could increase adipocyte lipolysis both in vivo and in vitro [28][29][30][31][32].…”
Section: Plos Onementioning
confidence: 84%
See 3 more Smart Citations
“…A study have showeded increased sympathetic activation and up-regulation lipolysis under hypoxia exposure [27]. Consistent with this hypoxia exposure for 14 days in mice significantly increased adipocyte lipolysis and elevated NEFA levels [1]. Several studies have also demonstrated that reduced oxygen supply in the air could increase adipocyte lipolysis both in vivo and in vitro [28][29][30][31][32].…”
Section: Plos Onementioning
confidence: 84%
“…TGs, which are composed of 3 fatty acids and 1 glycerol molecule, represent the most energy-dense lipolysis substrate [1]. In addition to adipocytes, almost all types of cells have the ability to store excess energy in the form of TGs in lipid droplets [34].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, some review studies have proposed exposure to hypoxic conditions, either passive or active in combination with exercise, as a promising tool to achieve health benefits [5][6][7][8], targeting hypoxia-inducible factor (HIF) and its signaling pathway as a novel therapeutic option to deal with various chronic diseases [9,10]. On the one hand, an oxygen-deprived (hypoxia) environment impairs cell adaptation and survival [11] with chronic exposure to severe hypoxia leading to hypoxemia and cardiovascular and pulmonary complications [12,13]. On the other hand, intermittent hypoxia (IH) has been shown to exert beneficial effects at the cardiovascular, metabolic, and cognitive levels, both in healthy and pathological individuals [14][15][16].…”
Section: Introductionmentioning
confidence: 99%